Settlement of Disputes on the Implementation of Registration of the Deed of Granting Mortgage Rights that Exceeds the Time Limit - Wirandari, Alfiah Dwi Ayu; Fajar Riyanto, Taufan (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
Those granting mortgage rights must be present before the PPAT, if for some reason they cannot appear in person, they must appoint another party as their attorney with a Power of Attorney to Charge Mortgage Rights (SKMHT) which must be followed by a Deed of Granting Mortgage Rights (APHT) in accordance with Article 15 paragraph ( 3) Mortgage Rights Law no later than 1 (one) month after the SKMHT is signed. The aim of this research is to identify and analyze how to resolve disputes over the registration of mortgage rights that exceed the time limit and legal certainty for creditors in the case of registration of mortgage rights that exceed the time limit in the case of this research. The approach method used in this research is a sociological juridical approach. The research specifications used are analytical descriptive. The data collection techniques used were interviews and observation. The data analysis technique uses a qualitative descriptive analysis method by drawing conclusions inductively. The research results showed that there was a dispute over the registration of the Mortgage Rights Registration Deed which exceeded the time limit due to the disorganized administration of the Land Deed Making Official (PPAT) in this research. The solution in completing the registration of a deed granting mortgage rights that exceeds the time limit in this research is carried out by mediation to obtain a win-win solution or no one feels too disadvantaged, and legal certainty for creditors in the case of registering a deed granting mortgage rights that exceeds this time limit is concurrent. Keywords: Granting; Land; Registration; Mortgage; Solution.